Potential Combination Ethanol Extract Of Papaya Leaf (Carica Papaya L) And Soursop Leaf (Annona Muricata L) On The Death Of Ascaridia Galli Worm In Vitro - maulida aisshella; Yauwan Tobing Lukiyono; Irwan Sulistio; Agus Aan Adriansyah (Universitas Nahdlatul Ulama Surabaya, 2026)
Worm infestations are a significant public health issue, primarily caused by Soil Transmitted Helminths (STH). One of the most common parasites affecting poultry is Ascaridia galli, which causes ascariasis and results in weight loss and impaired growth in affected birds. This study aims to evaluate the anthelmintic effects of a combined ethanol extract of papaya leaf and soursop leaf on the mortality of Ascaridia galli in vitro. We employed a quantitative, experimental laboratory approach using a Posttest-Only Group Design to determine the efficacy of the combined extracts as a treatment for Ascaridia galli. Each treatment group consisted of 7 worms, and the experiment was repeated 6 times with exposure times of 2, 4, and 6 hours. The data collected were analyzed using probit regression to assess the potential of the combined ethanol extracts of papaya and soursop leaves on the mortality rates of Ascaridia galli. The effectiveness of the extracts was evaluated based on the LC50 (lethal concentration for 50% of worms) and LC50 (lethal time for 50% of worms). The study found that the LC50 values were 47.614% at 2 hours, 20.549% at 4 hours, and 8.091% at 6 hours, while the LC50 values were 4.006 hours for 25% mortality and 1.536 hours for 50% mortality. These results indicate that the combined ethanol extracts of papaya leaf (Carica papaya L.) and soursop leaf (Annona muricata L.) show potential as an effective anthelmintic treatment against Ascaridia galli, with mortality rates increasing with longer exposure times and higher concentrations. Keywords: Papaya Leaf, Soursop Leaf, Anthelminthic, Ascaridia galli